Die geestesvertraagde kind en die gemeenskapsverpleegkundige - M.E. Norrish (AOSIS, 1980)
As a member of the health team the community health nurse is in a key position to play an important role in the prevention of mental retardation and in the rehabilitation and support which is necessary. The work is of such a nature that she meets the mother and the child both in the formal setting of the clinic and in the more informal atmosphere of the home visit. She does therefore have an invaluable opportunity for observation and discussion at a personal level, which is not always possible for other members of the multidisciplinary team.